Experimental determination of the parameters of the methodology for investigating the frost strength bond of soil and foundation material - A. V. Boyarintsev; E. K. Kozlikin; S. A. Kozelskikh (Vestnik MGSU)
Introduction. Freezing strength is a strength characteristic of frozen soils that describes their mechanical interaction with underground structures of buildings and structures. This characteristic is used in determining the bearing capacity of piles located in the zone of permafrost, and in assessing the pull-out effect of the tangential forces of frost heaving of seasonally frozen soils. The strength of freezing is determined by laboratory experiments, through the implementation of a shift of frozen soil relative to the material being tested. There are several different methods for determining the freezing strength, but all of them have some disadvantages: some are cumbersome and difficult to carry out; in others it is impossible to simulate all types of soil freezing conditions.Materials and methods. To study the freezing strength of glass-reinforced plastic with a frozen soil specimen, the Department of Geotechnics of SPbGASU proposed a new method for determining the freezing strength of soil and underground structures, which makes it possible to reduce the labour intensity of testing, minimize the additional impact on the tested soils during their preparation, and also take into account the peculiarities of soil freezing around the foundation. However, like any new method, it has a number of uncertainties. In the framework of this study, the optimal parameters of the method were experimentally established: the ratio of the diameter of the form to its height, the design of the support, as well as the method of insulation during freezing.Results. The shape of the tested specimen has a significant influence on the final value of the freezing strength, the construction of the support and the method of insulation of the specimens influence the obtained result during the test. The best solutions are: the use of a ring-shaped support that prevents mould movement and does not prevent ground movement, and the use of insulation by immersing the specimens in the insulation rather than wrapping them in it.Conclusions. A complete method for determining the frost strength bond of soil with underground structure material is presented, the reliability of the results obtained is superior to that of the data obtained by the GOST method, as shown by the lower value of the coefficient of variation within the results of the control sample of specimens.